URBAN HOUSING ENERGY CONSUMPTION ON PEATSWAMP Case: City dense peatland area in Palangka Raya - Yunitha; Mandarin Guntur (Jurusan Arsitektur UPR, 2015)
Population growth in combination with intensive energy consumption is the main driving force in urban area in developing countries that has caused impacts on socio-economic aspects, and environmental systems lead to green house gas (GHG) emissions into the atmosphere. Indirectly, life style and consumption pattern of urban people are also affecting the impacts. Nowdays, the phenomenon of global warming is becoming major concerns in environmental management. Urban planners and policy makers are being to minimize dan reduce the impacts of energy consumption and GHG emission when they are planning the cities. It is important to understand urban form as element in the city planning process and relationship between urban form, energy, and the environmental impacts to establish effective strategies to meet environmental goals (Anderson, 1996). Urban residential density is the main factor contributing to urban form. Therefore, dealing with energy use and carbon emissions related to climate change in urban environment, especially in residential sector is one of the challenges due to its unfavourable effect on the ecosystem. This study aims at determining factors contributing, particularly at the local level and also identifying the responses from citizen and local government regarding to energy consumption and carbon emissions in urban residential development on peatland area. The results will bring some recommendations on better measures for urban residential that will be develop on the peatland area particularly in Kalimantan Tengah, Indonesia related to carbon emission and energy use for present day and for next generation.